Watthanatham m̄ưang : sarup Kānsammanā thāng Wichākān r̄ưang "Watthanatham M̄ưang: Chumchon M̄ưang læ Kānplīanpl̄æng nai Krung Thēp-- læ Parimonthon", 7-8 Karakadākhom 2537 (Sūn Mānutsayawitthayā Sirinth̨ōn, Mahāwitthayālai Sinlapāk̨ōn, 1994)
Proceedings of seminar on impact of urbanization to communities culture and social structure in Bangkok metropolitan and vicinity areas.